The Effect Of Carbon Dots On Conductive Ink As A Vitamin C Electrochemical Sensor - Lee, Mun Yi (Universiti Sains Malaysia, 2021)
The demand for portable and disposable electrochemical sensors using conductive ink is increasing due to its flexibility and conductivity. With the recent discovery of carbon dots and its conductivity improvement, it can be modified as an additives in the conductive ink to see its effect as an electrochemical sensor towards vitamin C. In this study, an easy and inexpensive fabrication of unsupported sensor strips using carbon black (CB) as filler and alternate different binder such as polyvinyl alcohol (PVA) and polymethyl methacrylate (PMMA) was fabricated. The conductive ink prepared was casted on non-woven cloth using membrane casting tool and allowed to cured. It was then cut into standard sizes for characterization as well for cyclic voltammetry (CV) for vitamin C detection. The optimum of the conductive ink was 6:4 (m:m) CB: PVA, with higher molecular weight (MW) and hydrolysis degree (DH) of PVA. Crosslinking of PVA was not needed as it will decrease the conductivity of the ink. The lowest resistivity obtained for CB/PVA and CB/PMMA sensor strips were 0.357 ± 0.03 Ω·cm and 2.735 ± 0.2 Ω·cm which show CB/PVA conductive ink has more potential than CB/PMMA conductive ink and even commercial ink. The blending of carbon dots (CDs) was able to decrease the resistivity at optimum amount. However, CB/PVA sensor strip was not able to produce any oxidation and reduction peak in CV showing its non-responsiveness towards detection of vitamin C while CB/PMMA sensor strip was able to measure the vitamin C presence with limit of detection (LOD) of 0.622 mM and linear range of 5 – 15 mM. CDs was coated on CB/PVA and CB/PMMA sensor strips surface but only adhere to CB/PMMA which may due to porous structure of CB/PMMA sensor strip while detaching of CDs observed for CB/PVA. The CDs coated on the surface was able to decrease the resistance up to 36% for both sensor strips and increase the background current of CB/PMMA CV response showing improved conductivity. However, the peak current response decreased due to repulsion reaction of same negative charge of vitamin C and the carboxyl groups on CDs surface. Therefore, the CDs modification was deduced only suitable for detecting positive charge analyte. The proposed sensor strips exhibited great stability with a 10-cycles CV run in neutral, acidic but decent performance in alkaline condition.